INCORPORATING THE FRACTAL DISTRIBUTION OF FAULTS AS A MEASURE OF FAILURE CONCENTRATION - Smirnov V.B.; Zaviyalov A.D. (My University, 1997)
The effect of the random spatial distribution of earthquake-generating faults on the estimation of the failure concentration parameter is investigated. It is shown that on the assumption of a fractal distribution of faults the failure concentration parameter is a power function of the size of a space in which this parameter is estimated. The power is defined by the fractal dimension of fault distribution in the space considered. It is proposed that a calculated fault concentration parameter should be corrected for fault distribution nonuniformity taking into account variations of the fractal dimension of the parameter in different seismic areas and different time periods.